Hypopharyngeal carcinoma: a clinical study (Bangladesh Journal of Otorhinolaryngology, 2009)
A prospective study was carried out from 2001 to 2002 at Department of Otolaryngology and Head- Neck Surgery, BSMMU, DMCH, SSMC & Mitford Hospital, Dhaka. Data were collected from 45 patients with histologically diagnosed hypopharyngeal carcinoma on the following variables 1) sociodemographics, 2) clinical manifestations, 3) sub-sites of carcinoma, 4) clinical staging, 5) time of diagnosis, 6) associated risk factors, and 8) patients general performance status at presentation was determined by the Karnofsky scoring system. Results of this study showed that hypopharyngeal carcinoma affects fourth (60%) and fifth (26.7%) decade of life. It was found that male was highly predominant to develop hypopharyngeal carcinoma and ratio was 6:1. People with lower educational level and lower income group were found to be affected more by hypopharyngeal carcinoma. In this study the mean time elapsed from the appearance of the first symptom to the diagnosis of hypopharyngeal carcinoma was 4.11 months. This study found that the key symptom of hypopharyngeal carcinoma was dysphagia, pain, hoarseness and neck mass. 80 percent patient presented with palpable lymph node and all of them were in level II. Pyriform fossa was found to be the commonest site (80%) affected by carcinoma. In this series 75 percent patient presented in stage III and stage IV. There is strong relation between staging and diagnostic delay (p